2020
DOI: 10.3390/jtaer16030022
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perceived Risk Dimensions on e-Shopping Behavioural Intention among Women—A Family Life Cycle Stage Perspective

Abstract: The relationship between perceived risk and behavioral intention (BI) in e-shopping, based on family life cycle (FLC) stages, has been analyzed in this work. Although FLC stages are considered to have a better predictive ability than age, few e-shopping studies have concentrated on understanding its effects. This study, as a pioneering effort, has divided Indian women based on nine FLC stages and has studied the role of ten dimensions of perceived risk on BI to shop online across each life cycle stage. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 116 publications
0
32
0
Order By: Relevance
“…Behavioral intention is a variable analyzed in many papers [24][25][26][27][28][29][30][31] in relation to different behaviors. Even though this term is specific to psychology, it has multiple applications in other fields.…”
Section: Behavioral Intentionmentioning
confidence: 99%
“…Behavioral intention is a variable analyzed in many papers [24][25][26][27][28][29][30][31] in relation to different behaviors. Even though this term is specific to psychology, it has multiple applications in other fields.…”
Section: Behavioral Intentionmentioning
confidence: 99%
“…Theory of reasoned action (TRA) depicts that BI to use the Internet for shopping is dependent upon shopper's attitude toward online buying (Amirtha et al, 2021;Choi, & Park, 2020). BI represents an individual's readiness toward e-shopping and theoretically, it is an antecedent to offline purchasing behavior (Hassan et al, 2021).…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
“…Moreover, the level of privacy that an individual prefers also decides his perception and readiness toward digitalization. If they prefer more privacy, they resist and if the level is not too high, they are flexible (Amirtha et al, 2021;Joshi et al, 2017). For instance, if we talk about security threats or perceived risks, there are frauds like credit card frauds, there is a fear of losing important data, intrusion of viruses, and so on.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Perceived risk is well-defined by Dowling and Staelin (1994) as something that creates doubt in the consumer's mind to buy any specific goods or services. It has been demonstrated that perceived risk in consumer behavior is much more of an issue now than it has been in the past (Amirtha et al, 2021).…”
Section: Perceived Risk and Disadvantages Of Online Shoppingmentioning
confidence: 99%